Clathrin adaptor AP1B controls adenovirus infectivity of epithelial cells - Diaz, Fernando (National Academy of Sciences, 2009)
Adenoviruses invading the organism via normal digestive or respiratory routes require the Coxsackie-adenovirus receptor (CAR) to infect the epithelial barrier cells. Because CAR is a component of tight junctions and the basolateral membrane and is normally excluded from the apical membrane, most epithelia are resistant to adenoviruses. However, we discovered that a specialized epithelium, the retinal pigment epithelium (RPE), anomalously expressed CAR at the apical surface and was highly susceptible to adenovirus infection. These properties of RPE cells correlated with the absence of the epithelial-specific clathrin adaptor AP1B. Furthermore, knockdown of this basolateral sorting adaptor in adenovirus-resistant MDCK cells promoted apical localization of CAR and increased dramatically Adenovirus infectivity. Targeting assays showed that AP1B is required for accurate basolateral recycling of CAR after internalization. AP1B knock down MDCK cells missorted CAR from recycling endosomes to the apical surface. In summary, we have characterized the cellular machinery responsible for normal sorting of an adenovirus receptor and illustrated how tissue-specific variations in such machinery result in drastic changes in tissue-susceptibility to adenoviruses.